2017
DOI: 10.1155/2017/6435138
|View full text |Cite
|
Sign up to set email alerts
|

Multiuser Searchable Encryption with Token Freshness Verification

Abstract: A Multiuser Searchable Encryption (MUSE) can be defined with the notion of Functional Encryption (FE) where a user constructs a search token from a search key issued by an Enterprise Trusted Authority (ETA). In such scheme, a user possessing search key constructs search token at any time and consequently requests the server to search over encrypted data. Thus, an FE based MUSE scheme is not suitable for the applications where a log of search activities is maintained at the enterprise site to identify dishonest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(186 reference statements)
0
6
0
Order By: Relevance
“…In 2013, Fang et al [14] proposed a PEKS scheme in the standard model, which can resist outside attacker's offline KGA. Later, many researchers studied the offline KGA and proposed many schemes [15][16][17][18][19][20].…”
Section: Related Workmentioning
confidence: 99%
“…In 2013, Fang et al [14] proposed a PEKS scheme in the standard model, which can resist outside attacker's offline KGA. Later, many researchers studied the offline KGA and proposed many schemes [15][16][17][18][19][20].…”
Section: Related Workmentioning
confidence: 99%
“…However, PEKS often has much more computation overheads than SSE due to doing paring computations. There are more recent works for improving security [17,18], improving functionality [19,20], and improving performance [21] for the PEKS. Boneh et al showed that PEKS implies IBE [13].…”
Section: Related Work Querying On Encrypted Data Is a Long-termmentioning
confidence: 99%
“…To solve the problem, there are mainly two kinds of measures according to whether or not a trusted third party (TTP) exists. The TTP manages the user's key which helps a user to generate the trapdoor when the user wants to search on the encrypted data from a data owner [35]- [37]. The schemes without TTP usually either need to predetermine the users and pre-compute some parameters by all the users [38]- [40], or let the data owner play a role of TTP [41].…”
Section: A Related Work and Our Contributionsmentioning
confidence: 99%